2001
DOI: 10.1054/bjoc.2001.2079
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MAGE-A3 in breast cancer patients’ sentinel lymph nodes

Abstract: SummaryThe detection of occult metastatic breast cancer cells by RT-PCR is limited by the poor specificity of most tumour mRNA markers. MAGE-A3 is a highly specific tumour mRNA marker that is not expressed in non-cancer cells. This study assesses MAGE-A3 mRNA as a molecular marker for the detection of tumour cells in the sentinel lymph nodes (SLN) of breast cancer patients. Serial frozen sections of SLN (n = 121) were obtained from 77 AJCC (American Joint Committee on Cancer) Stage I-IIIA breast cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 49 publications
1
13
0
2
Order By: Relevance
“…Also, MAGE-A-positive cases were often with high histological grade and metastatic axillary lymph nodes, which strengthened the association between MAGE-A and cancer progression. According to some studies, MAGE-A proteins have to do with negative hormone receptor status, high histologic grade [37,39], large tumor size (≥2cm) [36], positive sentinel lymph nodes (SLN) [40], high Ki-67 score [27] and HER-2 negativity. Notably, MAGE-A expression is contributed to unfavorable outcomes and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MAGE-A-positive cases were often with high histological grade and metastatic axillary lymph nodes, which strengthened the association between MAGE-A and cancer progression. According to some studies, MAGE-A proteins have to do with negative hormone receptor status, high histologic grade [37,39], large tumor size (≥2cm) [36], positive sentinel lymph nodes (SLN) [40], high Ki-67 score [27] and HER-2 negativity. Notably, MAGE-A expression is contributed to unfavorable outcomes and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…They have the advantage of a higher sensitivity and the possibility of researching not only single sections of a lymph node in a single examination. RT-PCR is a rapidly developing technique, which has been successfully applied to the investigation of micrometastases of many solid, malignant, tumours such as: gastric cancer, colorectal cancer, prostate cancer, breast cancer, pancreatic cancer [36][37][38][39][40][41][42][43][44]. In gastrointestinal cancers, detection of micrometastases by molecular methods, in histopathologically negative lymph nodes, was the most important factor indicating a possibility of local relapse and the need for more aggressive treatment [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The study additionally revealed that overexpression of one or more tumor mRNA markers in the SN correlated with poor prognostic clinicopathologic factors. In another study from our institution, Wascher et al [24] used MAGE-A3, a highly specific tumor mRNA marker not expressed in non-cancer cells, as a single tumor marker in RT-PCR with high specificity. More recently, Gillanders et al [25••] provided further evidence that multimarker RT-PCR is a valid surrogate for detection of occult micrometastasis in the axillary lymph node.…”
Section: Histopathologic and Molecular Assessment Of The Sentinel Nodementioning
confidence: 99%